- ( Study for the period (2000-2018- China's investment policy in povertyeradication (Journal of Economic Additions, 2020)
This study aims to demonstrate the contents and effectiveness of China's investment policy against poverty. To achieve the objectives of study, a descriptive analytical approach was adopted to trace effects of the adopted policy in poverty reduction. The study concluded the extent of adopted investment policy effectiveness to affect macroeconomic levels and the consequent impact on poverty rates which declined to low levels, especially in (2000-2018), and the best evidence is statistics of important international organizations, especially the World Bank, This reflects Chinese policy’s success in lifting hundreds of millions out of poverty, thus gaining praise from international community, making it a model for the developing world.Keywords: Investment Policy, China, Poverty.